Pemberdayaan Penyandang Disabilitas Fisik Melalui Keterampilan Seni Kriya di Yayasan Disabilitas Indonesia Satu Jakarta Timur - Apriliani, Zahra; Heraerah, Abu (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
This research aims to describe the empowerment process, supporting and inhibiting factors, results achieved, and the theoretical and practical implications of social work in empowering people with physical disabilities through the arts and crafts skills program at the Indonesia Satu Disability Foundation. This research uses a descriptive method with a qualitative approach. In this research, the data source or sample that the author chose was Nonprobability Sampling with Purposive Sampling technique. The data collection techniques used in this research are observation, interviews, and document study with data analysis techniques, namely Data Coding. This research produces an overview of the program process for empowering people with physical disabilities through the arts and crafts skills program at the Indonesia Satu Disability Foundation through the initial stages, namely collaborating with stakeholders and determining program objectives. Then the implementation stage begins with the assessment, intervention or program implementation stage which consists of skills training and technical guidance, the next stage is monitoring and evaluation, and the final stage is termination. In the empowerment process there are supporting and inhibiting factors. Internal supporting factors are one's own intentions, participation of other members, and full support from the foundation. External supporting factors include company CSR support and disability volunteers. The inhibiting factors in implementing this program are feeling lazy and not being used to doing the skills. Efforts are being made to overcome these obstacles so that empowerment can run according to the objectives of the empowerment program, namely increasing enthusiasm for skills training and increasing consistency in carrying out skills. The practical implications of social work in empowerment programs for physical disabilities through craft skills are through the role of social workers as facilitators, brokers and enablers. Practical implications also use social work principles consisting of acceptance, individualization, and self-determination and using social work skills consisting of communication and assessment. The theoretical implication of using social work methods applied in implementing this empowerment program is Social Group Work, namely implementing empowerment programs in groups.